The Strengthening Innovation and Information Technology Capabilities in Vocational Schools as An HRD Enter Point to Improve the Performance of SMEs - Iffah Budiningsih; Tjiptogoro Dinarjo Soehari; Fufung Alfulailah (Jurnal Pendidikan Teknologi dan Kejuruan, 2021)
The purpose of this research is to show whether it is necessary to strengthen the capabilities of the innovation and informatics technology among vocational school students who will later become human resources enter points that can improve the performance of the SMEs industry in the digital era. We know that the SMEs industry is one of the pillars of Indonesia's economic development that spearheads job creators, and vocational graduates are expected to be the driving force for the achievement of SME optimal performance. This research relied on quantitative explanatory with survey method; its sample involved 176 out of 758 merchants (the total population) in Pasar Glodok Jakarta. All data were analyzed using descriptive and regression analysis with the SPSS program. The results showed that: (a) the ability innovating and the information technology of SME entrepreneurs is the dominant factor determining the achievement of optimal SME performance, with a correlation value = 0.79.5 or 0.8 (strong correlation); (b) Innovation and information technology skills contribute to the performance attainment of SME entrepreneurs in the research site by 63.2%; the remaining 36.8% is determined by factors not included in the study; (c) Innovation and information technology capabilities are the capabilities needed by SMEs human resources in achieving optimal business performance; (d) it is necessary to strengthen the ability of innovation and information technology since school (especially Vocational schools) in a sustainable manner which will become the key point of SMEs industry's human resources as an effort to bring closer the concept of link and match between educational institutions and industry.